The Influence of Regional Original Income and Capital Expenditure on Regional Financial Independence in Regency/City Governments of South Sumatra Province - Chairani Adelina; Meirani Betriana (CV Edujavare Publishing, 2026)
This study aims to determine the effect of local revenue and capital expenditure on the financial independence of local governments in South Sumatra Province. This study uses a quantitative approach and quantitative data types with secondary data sources obtained from the Regional Government's Financial Report (LKPD) of South Sumatra Province for 2021-2023. Data were processed using SPSS and analyzed using multiple linear regression analysis. The results of this study indicate that local revenue influences regional financial independence with a significance value of 0.00 <0.05, while capital expenditure has a significant negative effect on regional financial independence with a value of 0.001 > 0.05. However, local taxes and regional levies simultaneously influence regional financial independence with a significance value of 0.00 <0.05 and a coefficient of determination of 93.4%.